Antibiotic-loaded tantalum may serve as an antimicrobial delivery agent. (July 2019) - Sautet, P.; Parratte, S.; Mékidèche, T.; Abdel, M. P.; Flécher, X.; Argenson, J-N.; Ollivier, M.
Abstract : Aims: The aims of this study were to compare the mean duration of antibiotic release and the mean zone of inhibition between vancomycin-loaded porous tantalum cylinders and antibiotic-loaded bone cement at intervals, and to evaluate potential intrinsic antimicrobial properties of tantalum in an in vitro medium environment against methicillin-sensitive Staphylococcus aureus (MSSA). Materials and Methods: Ten porous tantalum cylinders and ten cylinders of cement were used. The tantalum cylinders were impregnated with vancomycin, which was also added during preparation of the cylinders of cement. The cylinders were then placed on agar plates inoculated with MSSA. The diameter of the inhibition zone was measured each day, and the cylinders were transferred to a new inoculated plate. Inhibition zones were measured with a Vernier caliper and using an automated computed evaluation, and the intra- and interobserver reproducibility were measured. The mean inhibition zones between the two groups were compared with Wilcoxon's test. Results: MSSA was inhibited for 12 days by the tantalum cylinders and for nine days by the cement cylinders. At day one, the mean zone of inhibition was 28.6 mm for the tantalum and 19.8 mm for the cement group (p < 0.001). At day ten, the mean zone of inhibition was 3.8 mm for the tantalum and 0 mm for the cement group (p < 0.001). The porous tantalum cylinders soaked only with phosphate buffered solution showed no zone of inhibition. Conclusion: Compared with cement, tantalum could release antibiotics for longer. Further studies should assess the advantages of using antibiotic-loaded porous tantalum implants at revision arthroplasty. Cite this article: Bone Joint J 2019;101-B:848–851.